2016
DOI: 10.1111/bjc.12120
|View full text |Cite
|
Sign up to set email alerts
|

Psychological need satisfaction, control, and disordered eating

Abstract: Our results indicate that young women with chronically unfulfilled basic psychological needs might be vulnerable to developing disordered eating behaviours. The observed patterns suggest that persistent experience of need frustration may engender an internal sense of ineffectiveness and lack of control, which then compels individuals to engage in disordered eating behaviours in an attempt to regain autonomy and competence. Interventions for eating disorders may be most effective when emphasizing the promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…Fourth, the MTurk sample used in the present study might not be generalizable to the population as a whole. Note, however, that previous research has found similarities in the factors that are associated with body dissatisfaction/disordered eating in MTurk samples, student samples, and community samples (Froreich, Vartanian, Zawadzki, Grisham, & Touyz, ; Vartanian et al, ). Finally, the current study focused on associations with disordered eating, but it is possible that the model described in this paper has broad applicability to a range of psychopathologies.…”
Section: Discussionmentioning
confidence: 88%
“…Fourth, the MTurk sample used in the present study might not be generalizable to the population as a whole. Note, however, that previous research has found similarities in the factors that are associated with body dissatisfaction/disordered eating in MTurk samples, student samples, and community samples (Froreich, Vartanian, Zawadzki, Grisham, & Touyz, ; Vartanian et al, ). Finally, the current study focused on associations with disordered eating, but it is possible that the model described in this paper has broad applicability to a range of psychopathologies.…”
Section: Discussionmentioning
confidence: 88%
“…Participants were adult women based in the United States who were recruited through the Amazon Mechanical Turk (MTurk) website. MTurk is an online data collection method that has been shown to produce data that are comparable in quality and reliability to those provided by student and community samples [ 28 , 29 ]. Individuals who are registered with MTurk have access to a range of tasks that they can complete for small monetary incentives.…”
Section: Methodsmentioning
confidence: 99%
“…Some risk factors that are shared between these behaviors are more pertinent for one or the other, and this pattern may extend to the functions of the behaviors. For example, depressive and anxiety symptoms are elevated in both NSSI and ED populations, but are more strongly predictive of NSSI than of ED behaviors (Muehlenkamp et al, ; Vansteelandt et al, ), which instead tend to be preceded by interpersonal stressors and a need to regain or exert control (Froreich, Vartanian, Zawadzki, Grisham, & Touyz, ; Razenhofer et al, ). These findings tentatively suggest that emotional regulation functions may be more salient motivators for NSSI compared to ED behaviors, and social functions may be more relevant to motivating ED behavior but the lack of research explicitly testing this comparison makes it hard to draw definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%